Fiscal Multipliers in Bulgaria : Low But Still Relevant - Muir, Dirk (IMF Working Papers; Working Paper, 2013)
With fiscal adjustment proceeding quickly in Bulgaria and given the weak economic growth environment, there is keen interest in making the budget composition more growth friendly. This paper quantifies the short-term impact of fiscal policy on economic activity in Bulgaria using econometric and model-based approaches. While fiscal multipliers have been modest in the past, as can be expected in a small open emerging economy, the effect on output is not independent of the speed of adjustment and the specific consolidation measures used. The impact of fiscal policy on economic activity is larger in downturns than in expansions and capital spending and direct taxes are associated with the largest effects on output, while non-targeted government transfers and indirect taxes are associated with a smaller impact. The results suggest that increased capital spending financed by higher indirect tax revenue collections through base broadening has sizeable growth effects over the medium and long-term.